A study of factors affecting regression of βhCG in gestational trophoblastic disorders - Devasia, Neena; Philip, Tinu (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Gestational trophoblastic disorders are among the rare human tumors that can be cured even in the presence of widespread dissemination. Authors can anticipate the development of persistent trophoblastic disease by identifying high risk factors affecting βhCG regression in vesicular mole. The study of this aim was to determine the incidence of gestational trophoblastic disorders and persistent trophoblastic disease in our institution. Factors affecting regression of βhCG and thereby leading to persistent disease are assessed. Methods: The study was conducted for a period of 2 years at a tertiary care centre in central Kerala. The factors affecting progression to persistent disease are assessed by a case control study. Those developing persistent trophoblastic disease were taken as cases and those with normal regression of βhCG were taken as controls. Variables studied were age, sociodemographic factors, obstetric history, histopathological report, βhCG value, post evacuation USG and clinical features. Results: The incidence of gestational trophoblastic diseases was 1 in 178 births and of persistent trophoblastic disease was 18.6%. Fourteen cases with persistent trophoblastic disease were studied and 61 controls were recruited. Incidence increased in older age group (>30) and low socio-economic group. Pre-evacuation βhCG> 40000 and presence of theca lutein cyst are important factors affecting βhCG regression. Strong association with uterine size >poa, post evacuation uterine subinvolution and presence of hyperthyroidism was found. Conclusions: Progression to persistent trophoblastic disease was associated with low socioeconomic status, high pre-evacuation βhCG values, uterine size>poa and presence of theca lutein cysts. Identification of these risk factors helps in proper counseling and meticulous follow up of patients.